Analysis of Risk Factors and Prevention of Stunting In Early Childhood In Rural Areas - Fransisca, Vika; Astuti, Aurelia Widya (Al Makki Health Informatics Journal, 2024)
Stunting remains a significant public health concern, particularly in rural areas where socio-economic and environmental factors exacerbate the problem. This study aims to analyze the risk factors contributing to stunting in early childhood and propose effective prevention strategies tailored to rural contexts. Utilizing a descriptive-analytic approach with a cross-sectional design, data were collected from 300 households through structured questionnaires, in-depth interviews, and direct observations. Logistic regression analysis identified maternal education, household income, dietary diversity, and sanitation access as critical determinants of stunting. Qualitative data highlighted economic pressures and limited nutritional knowledge as additional barriers. The findings emphasize the importance of integrated, community-driven interventions focusing on maternal education, exclusive breastfeeding, and improved sanitation. This research contributes to the existing literature by providing a comprehensive framework for addressing stunting in rural areas and offers actionable recommendations for policymakers and community stakeholders. Future studies should explore the long-term impact of these interventions and the role of cultural dynamics in sustaining their effectiveness.